Dr med. Kazimierz Bartkowiak (1921-2007) Wspomnienie w 10. rocznicę śmierci - Krawczyński, Marian (Pediatria Polska - Polish Journal of Paediatrics, 2017)
In reminiscence, a short biography of Kazimierz Bartkowiak, a pediatrician in Poznań, is presented. His professional and scientific activity has been in place on second half of the 20th century. His professional interests were focused on pediatric endocrinology, conge¬nital malformations and social pediatrics.